AKTUALISASI FALSAFAH KALAM DALAM KONTEKS KEKINIAN - Kholil, Ahmad (ULUL ALBAB Jurnal Studi Islam, 2010)
Islamic theology, as one cluster of Islamic knowledge is a product of thought in certain cultural social environment. Therefore, everything related to it is no longer appropriate today. The knowledge gives so it can solve life's problems that start to threaten human existence, practice, good deeds, a substantive meaning to the religious doctrine and social harmony. The knowledge such as Islamic knowledge, philosophy, and theology must have been oriented to humanity problems. They are already completed with natural phenomena, social and cultures which have been always develop. We hope that Islamic studies won't miss actuality which has been released from humanity dimensions.